Ubiquitous Conjugative Mega-Plasmids of Acinetobacter Species and Their Role in Horizontal Transfer of Multi-Drug Resistance - Mindlin, Sofia; Maslova, Olga; Beletsky, Alexey; Nurmukanova, Varvara; Zong, Zhiyong; Mardanov, Andrey; Petrova, Mayya (Frontiers in Microbiology, 2021)
Conjugative mega-plasmids play a special role in adaptation since they carry a huge number of accessory genes, often allowing the host to develop in new niches. In addition, due to conjugation they are able to effectively spread themselves and participate in the transfer of small mobilizable plasmids. In this work, we present a detailed characterization of a recently discovered family of multiple-drug resistance mega-plasmids of Acinetobacter species, termed group III-4a. We describe the structure of the plasmid backbone region, identify the rep gene and the origin of plasmid replication, and show that plasmids from this group are able not only to move between different Acinetobacter species but also to efficiently mobilize small plasmids containing different mob genes. Furthermore, we show that the population of natural Acinetobacter strains contains a significant number of mega-plasmids and reveal a clear correlation between the living conditions of Acinetobacter strains and the structure of their mega-plasmids. In particular, comparison of the plasmids from environmental and clinical strains shows that the genes for resistance to heavy metals were eliminated in the latter, with the simultaneous accumulation of antibiotic resistance genes by incorporation of transposons and integrons carrying these genes. The results demonstrate that this group of mega-plasmids plays a key role in the dissemination of multi-drug resistance among Acinetobacter species.